A survey on losing weight in Japanese professional boxers - Kobayashi, G.; Kida, N. (Journal of Physical Education and Sport, 2022)
The deprivation of Boxing titles and match cancellation due to being overweight have often occurred in recent professional boxing competitions. This study examined the effects of weight loss on professional boxers` psychological conditions. The subjects were 122 professional boxers (mean age= 24.95±4.4 years old) having a Japan Boxing Commission license. We conducted an online or postal self-administered questionnaire survey. The survey inquired about basic information, including age, height, usual weight, class, and competition history, and about (1) positive and (2) adverse effects of weight loss on psychological conditions. We extracted text data of participants' descriptions and categorized and subcategorized them based on discussions between the author and co-researchers to ensure objectivity. We used Steps for Coding and Theorization (SCAT; Oya, 2008), a qualitative data analysis method, to analyze weight loss's positive and negative effects on psychological conditions. This study concludes that we organized free descriptions, indicating two categories of negative effect: [reduced mental energy] and [evoking negative emotions] and three categories of positive effect: [improving competitive motivation], [improving self-confidence], and [improving concentration]. However, the positive results might have been produced by pre-match conditions rather than by weight loss, and it isn't easy to distinguish between them. Although 71% of the participants described positive effects, they might have confused their pre-match changes in their condition with the effects of weight loss. Consequently, weight loss might have had only adverse psychological effects, such as [reduced psychic energy] and [evoking negative emotions]. Furthermore, providing psychological support to pro boxers` motivations, emotions, and cognition would be helpful when losing weight.